Self-Rated Health and Inflammation: A Test of Depression and Sleep Quality as Mediators - Uchino, Bert N. (Psychosom Med, 2019)
OBJECTIVE: Despite its simplicity, single-item measures of self-rated health have been associated with mortality independent of objective health conditions. However, little is known about the mechanisms potentially responsible for such associations. This study tested the association between self-rated heath and inflammatory markers as biological pathways, and whether sleep quality and/or depression statistically mediated such links. METHOD: Eighty-six heterosexual married couples completed a standard measure of self-rated health, the CES-Depression scale, and the Pittsburgh Sleep Quality Index. Participants also had blood drawn for determination of plasma levels of IL-6 and hs-CRP. The Monte Carlo method was used to construct confidence intervals for mediation analyses. RESULTS: Results indicated that poor self-rated health was associated with higher CRP levels (B=.31, SE=.14, p=.028). Importantly, Monte Carlo mediational analyses showed that these results were statistically mediated by sleep quality (aXb=0.10, 95% CI [0.003, 0.217]) but not depressive symptoms (aXb=0.03, 95% CI [−0.03, 0.10]). CONCLUSIONS: These results highlight the biological and behavioral mechanisms potentially linking SRH to longer-term health outcomes. Such work can inform basic theory in the area as well as intervention approaches that target such pathways.